Loan, Its Forms and Types ("Journal "U". Economy. Management. Finance.", 2020)
This article discusses how the essence of credit is realized through the diversity of its forms and types. The systematization of existing approaches to the classification of forms and types of credit is made. The structure of lending in Russia at the present stage is considered.
Keywords: credit; lending; types of loans; forms of loans; bank; lender; borrower